Multiple Synchronous Tuberculous Aneurysms - D'cruz, Reuban; Chan, Dexter Y. S.; Ho, Pei (Journal of Clinical Interventional Radiology ISVIR, 2019)
The authors report a case of a 35-year-old woman with a medical history of recently diagnosed pulmonary tuberculosis presenting with chest and back discomfort. Chest radiograph demonstrated a bulky hilar mass, and computed tomography revealed multiple saccular aneurysms in the thoracic aorta, multiple fusiform aneurysms in the coronary arteries, left renal and splenic arteries, and right internal iliac pseudoaneurysms. Surgical management of the mycotic aneurysms was indicated in view of symptomatology. Thoracic endovascular aortic repair (TEVAR) and ascending aortic replacement with aortic valve suspension and coil embolization of right iliac artery pseudoaneurysm were performed. The coronary artery aneurysms were managed with surveillance.
Keywords: tuberculous; mycotic; aneurysms